EVALUASI PERATURAN PEMBEBANAN GANDAR KERETA API DI PULAU JAWA TERHADAP KONDISI AKTUAL - Muspitasari, Tri; Sulistyowati, Indah; Kumara, Widi (Jurnal Teknik Sipil, 2017)
Abstract: The railway structure includes a variety of constructions intended to supportrailroad and railway operations, one of which is a bridge. Locomotives are self-rail vehiclesthat function as rod or train carriages. Locomotives in Indonesia, especially in Java Island,have varying axle loads and axle distances, thus causing an inward force change that works onthe railway structure. The live load working on the structure of the railway bridge is a loadderived from a railway circuit whose size is determined based on the loading scheme of the1921 Load Plan (RM 1921). With RM 1921 which has been established as a rule of Bridgethrough which a series of railways passing then at a certain point on the bridge girder lengthenswill cause an inner force such as the force of moment and latitude that changes in magnitudedepending on the location of the train circuit. However, the actual condition of axle load andaxle distance is not in accordance with RM 1921. To know the magnitude of force in(maximum moment) then required an analysis calculation that is using line of influence. Fromthe calculation result between actual locomotive and RM 1921, it can be concluded that theactual maximum force of the locomotive is 30.38% less than RM 1921, therefore RM 1921 isstill sufficient to be used in the current conditionÂ Abstrak: Struktur jalan rel meliputi bermacam-macam konstruksi yang dimaksudkan untukmendukung jalan rel dan pengoperasian kereta api salah satunya adalah jembatan. Lokomotifmerupakan kendaraan rel yang dapat bergerak sendiri berfungsi sebagai penggerak rangkaiankereta atau gerbong. Lokomotif di Indonesia khususnya di Pulau Jawa mempunyai bebangandar dan jarak gandar yang berbeda-beda, sehingga hal ini mengakibatkan terjadinyaperubahan gaya dalam yang bekerja pada struktur jalan rel kereta api. Beban hidup yangbekerja pada struktur atas jembatan kereta api adalah beban yang berasal dari rangkaian keretaapi yang besarnya ditentukan berdasarkan skema pembebanan Rencana Muatan 1921 (RM1921). Dengan RM 1921 yang sudah ditetapkan sebagai peraturan Jembatan yang dilalui olehrangkaian kereta api yang melintas maka pada suatu titik tertentu pada jembatan gelagarmemanjang akan menimbulkan gaya dalam seperti gaya momen dan lintang yang berubahbesarnya tergantung dari letak rangkaian kereta api. Akan tetapi, kondisi aktual beban gandardan jarak gandar tidak sesuai dengan RM 1921. Untuk mengetahui besarnya gaya dalam(momen maksimum) maka diperlukan suatu perhitungan analisis yaitu menggunakan garispengaruh. Dari hasil perhitungan antara lokomotif aktual dan RM 1921 diperoleh kesimpulangaya dalam (momen) maksimum lokomotif aktual lebih kecil 30,38% dari pada RM 1921, olehkarena itu RM 1921 masih memadai untuk dipakai pada kondisi saat ini.